(untitled) (Indonesian Journal of Islamic Economics and Business, 2018)
The change of economic structure has opened many opportunities and challenges for local governments, including East Java. In response to this situation, it is necessary to combine local investment with diversification in major economic sectors to improve regional economic resilience. The purpose of this paper is to map potencial supply-demand investment in East Java and to identify suitable investment instrument on account of local benefit. Quantitative method with index analysis and bayes is used to map potencial investment supply, whereas ratio model is used to describe the potency of local investment demand. There are five potencial areas ie Kab. Pacitan, Kota Batu, Kota Mojokerto, Kab. Mojokerto and Kab. Madiun whereas potencial local fund percentage is 37% of total investment. By making UMR as basis price, the public may contribute an active role in the development of investment in particular areas.